English Language Functions Used for Copywriting in Instagram Accounts of Hotel Industry in Solo Area - Putri, Nawangsih Edynna; Tyas, Maharani Ayuning (Surakarta English and Literature Journal, 2025)
The purposes of this research are to identify the functions of the English language contained in Instagram copywriting in hotel industry in Solo area and to analyze the dominant function found in that copywriting. This research was employed qualitative methods, particularly in the Simak Bebas Libat Cakap technique for the data collection process. Copywriting data was analyzed by Geoffrey Leech’s five functions of language. The findings show that five language functions appear in copywriting text including informational, directive, phatic, aesthetic, and expressive functions. The informational function dominantly appears in the copywriting texts. The pattern is mostly to give information about the hotel’s products, services, special offers, and facilities. It implies that English copywriting in Instagram accounts of 3-star hotels in Solo area is used for brand awareness.